INNOVATION CLITORIA TERNATEA INTO HERBAL TEA TO IMPROVING THE REGIONAL ECONOMY AFTER COVID-19 - SAPUTRA, ARYA; ASTUTI, WIWIN; SUHARDI, MUHAMAD (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
Clitoria ternatea is a blue monocotyledonous vine that has long been used as a decorative plant for gardens and hedges. This legume plant originates from tropical Asia, which has spread to tropical countries such as Indonesia. The COVID-19 pandemic has had a significant impact on the economy around the world, including Indonesia. The goal of achieving the business as an innovation in the use of butterfly pea flowers which has many benefits, being able to plan, build, implement and prepare financial reports for a business and being able to improve the economy of the surrounding community in this century of the COVID-19 pandemic by buying butterfly pea flowers. The data obtained will be analyzed qualitatively using descriptive methods. The data collection method used is by using primary data and secondary data. The innovation of processing Clitoria ternatea into herbal tea in Kepayang Village has great potential to improve the regional economy after the COVID-19 pandemic ABSTRAKClitoria ternatea merupakan tanaman merambat monokotil berwarna biru yang telah lama digunakan sebagai tanaman hias taman dan pagar tanaman. Tanaman polong-polongan ini berasal dari Asia tropis, kemudian menyebar ke negara tropis seperti Indonesia. Pandemi COVID-19 memberikan dampak yang signifikan terhadap perekonomian seluruh dunia, termasuk Indonesia. Tujuan tercapainya usaha sebagai suatu inovasi pemanfaatan bunga telang yang mempunyai banyak manfaat, mampu merencanakan, membangun, melaksanakan dan menyusun laporan keuangan suatu usaha serta mampu meningkatkan perekonomian masyarakat sekitar pada abad ini. pandemi COVID-19 dengan membeli bunga telang. Data yang diperoleh akan dianalisis secara kualitatif dengan menggunakan metode deskriptif. Metode pengumpulan data yang digunakan adalah dengan menggunakan data primer dan data sekunder. Inovasi pengolahan Clitoria ternatea menjadi teh herbal di Desa Kepayang berpotensi besar meningkatkan perekonomian daerah pasca pandemi COVID-19